Capacitism and music: discussions based on the experience report of a student with spasmodic dysphonia in a music degree course at a brazilian public university (Orfeu, 2023)
Capabilityism is understood as a form of prejudice directed at people with disabilities. The discussion on this topic is relatively new in higher education music courses. Therefore, this article aims to discuss capacitism and inclusion in the context of a Degree in Music course, based on the experience report of the author who has Spasmodic Dysphonia. The discussion was based on the literature found on the subject and the author's personal experience. The results point to how much the discussions about inclusion and ableism still move slowly within higher music education, despite the Laws, internal guidelines and university projects aimed at the inclusion of people with disabilities, disorders and rare syndromes. We hope that this work can contribute to the expansion of the specific bibliography in the area of ​​accessibility, inclusion and ableism, as well as in the training of music teachers in higher education with regard to diversity in the classroom.
Keywords: inclusion; capacitance; higher music education; spasmodic dysphonia